The first known virus isolates from Antarctic sea ice have complex infection patterns. Issue 4 (22nd February 2018) - Luhtanen, Anne-Mari; Eronen-Rasimus, Eeva; Oksanen, Hanna M; Tison, Jean-Louis; Delille, Bruno; Dieckmann, Gerhard S; Rintala, Janne-Markus; Bamford, Dennis H
Abstract: Viruses are recognized as important actors in ocean ecology and biogeochemical cycles, but many details are not yet understood. We participated in a winter expedition to the Weddell Sea, Antarctica, to isolate viruses and to measure virus-like particle abundance (flow cytometry) in sea ice. We isolated 59 bacterial strains and the first four Antarctic sea-ice viruses known (PANV1, PANV2, OANV1 and OANV2), which grow in bacterial hosts belonging to the typical sea-ice genera Paraglaciecola and Octadecabacter . The viruses were specific for bacteria at the strain level, although OANV1 was able to infect strains from two different classes. Both PANV1 and PANV2 infected 11/15 isolated Paraglaciecola strains that had almost identical 16S rRNA gene sequences, but the plating efficiencies differed among the strains, whereas OANV1 infected 3/7 Octadecabacter and 1/15 Paraglaciecola strains and OANV2 1/7 Octadecabacter strains. All the phages were cold-active and able to infect their original host at 0°C and 4°C, but not at higher temperatures. The results showed that virus–host interactions can be very complex and that the viral community can also be dynamic in the winter-sea ice. Abstract : Isolation, characterisation, host range and temperature adaptation of the first known Antarctic sea-ice virus isolates.